Where fatherlessness meets music therapy : "the importance of therapist & the uniqueness of music" - Charalampidis, Miltiadis (2014)
A great number of studies are supporting father’s vital contribution in the well-being of their children. Fatherlessness, on the other hand, is something that more and more children are experiencing, growing up in a single-parent family. This, usually, has a number of negative consequences in children’s development (e.g. low self-esteem, loneliness, mistrust, distress,no life model). Music therapy offers an alternative way of dealing with the issue of fatherlessness. With music the therapeutic alliance is taking place faster and in a more pleasant way (making/listening to music). Moreover, trusting and the negative emotions can be first expressed and experienced within musical events -i.e. improvisation. Music therapy it is also seem to be a way that can stop the Cycle of Repeated Behaviors (CoRB), and can set fatherless clients free from their parents choices, equipping them with courage and inspiration to build their own different and better future. The aim of this thesis is, to briefly sketch father-involvement & absence and its consequences in society and later generations (i.e. children), to provide links between music therapy and the issue of absent father (fatherlessness), and to suggest areas in need for further research on the topic of fatherlessness and music therapy. Information from the current literature (psychology, sociology, and music therapy) will be presented and discussed along with information given by professional clinicians; two music therapists from Finland (Helsinki and Oulu). Links between literature and clinical practice will be presented as well as directions for further research on music therapy and its connections to the issue of fatherlessness.